AMERICANIZATION BY CATHOLIC MEANS: FRENCH CANADIAN NATIONALISM AND TRANSNATIONALISM, 1889–1901. (12th April 2017) - Lacroix, Patrick
Abstract : The age of nationalities and nationalism associated with nineteenth-century Europe also found expression in North America in the same period: French Canadians developed a national consciousness charged with a religious and providential mission. As these Canadians crossed into the United States in ever-rising numbers and established permanent "colonies" during the Gilded Age, they carried with them a cultural ideology that kept them apart from mainstream American society—and apart from their Irish American coreligionists and coworkers. Claiming the freedoms promised to them by the Constitution, these immigrants from the North battled for accommodation not only in political conventions or state legislatures, but also in the Roman Catholic Church, whose leaders seemed intent on doing away with foreign languages and customs. The religious battle came to a head as lay and clerical Catholics gathered in Baltimore, in 1889, to reassert the Church's unity as well as its patriotic credentials. By drawing attention to French Canadian immigration, often overlooked in immigration studies, this article refocuses the question of Americanization on the Catholic Church, which proved one of the most powerful agents of acculturation in late nineteenth-century America.